Eshche k probleme "sportivnogo serdtsa" - Grayevskaya, N. D.; Goncharova, G. A.; Kalugina, G. E. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to discuss the problem of the rational frequency of miocardiac hypertrophy's evaluation and the comperative efficiency of the various method in its diagnosis. More than 1000 athletes had been inspected. The study's results had affirmed the effectiveness of the ultrasonic cardiography for the dynamic testing of athletes. the optimal way of a heart's adaptation to the demands of sports training is the left ventricle's miocardium mass increase by the moderate, even thickening of the miocardium and by increasing the left ventricle's cavity. The noticable degrees of the general heart volume' increase. as well as the increase of the left ventricle's and its partion volume (especially when uneven hypertrophy) demand the fised attention and the additional inspection.